Ferramentas utilizadas no planejamento e controle de obra - URSULINO, Vanessa Campagnoli (2021)
The building planning and control are indispensable processes for civil construction firms that demand decision-making improving, increase profits and get more efficiency on the resource management, like labor, equipment, supplies and time. The tools that allow this process are essentially to get that results, because, since the data collected are properly used, people that are involved in the process can get essentially information to make the right decision. Analyzing these tools, it can be possible to identify which tool can be applied in different requirements as making schedule, continuous improvement process, better resource utilization, with the objective of improving the building execution efficiency.